ROUSSEAU'S INFLUENCE ON MODERN EDUCATIONAL THOUGHT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Education plays a fundamental role in shaping individuals and societies, and throughout history, various philosophers have offered insights into the nature and purpose of education. One such philosopher whose ideas have had a lasting impact is Jean-Jacques Rousseau. Rousseau's philosophy of education emerged during the Enlightenment period and challenged traditional approaches to schooling by emphasizing the natural development and innate goodness of the child. Understanding the background and context of Rousseau's philosophy is essential for comprehending its significance in educational thought and practice.